A pre-clerkship simulation-based procedural skills curriculum: decreasing anxiety and improving confidence of procedural skill performance - Frank Battaglia (Canadian Medical Education Journal, 2021)
Introduction: Pre-clerkship procedural skills training is not yet a standard across Canadian medical school curricula, resulting in limited exposure to procedures upon entering clerkship. While simulated skills training has been documented in the literature to improve performance in technical ability, anxiety and confidence have yet to be investigated despite their documented impact on performance and learning. This study therefore aims to evaluate the effect of pre-clerkship procedural skills training on medical student anxiety and confidence.